2019
DOI: 10.1080/15459624.2019.1639719
|View full text |Cite
|
Sign up to set email alerts
|

Particle size and metal composition of gouging and lancing fumes

Abstract: Work Exposures and Health in 2017. Annals of Occupational Hygiene requires that references in the text should be as follows: Jones (1995), or Jones and Brown (1995) or Jones et al. (1995) for more than two authors. References are listed in alphabetical order by name of first author, using Vancouver Style of abbreviation and punctuation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 97 publications
1
5
0
Order By: Relevance
“…For all size fractions, and especially for UFPs, these results evidence the need for a detailed understanding of incidental particle formation mechanisms due to their direct implications on particle composition and, thus, exposure. In agreement with recent studies ( Keyter et al , 2019 ), it is advisable that the ultrafine size fraction (especially, incidental) should be included in personal exposure and risk assessments in occupational settings.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…For all size fractions, and especially for UFPs, these results evidence the need for a detailed understanding of incidental particle formation mechanisms due to their direct implications on particle composition and, thus, exposure. In agreement with recent studies ( Keyter et al , 2019 ), it is advisable that the ultrafine size fraction (especially, incidental) should be included in personal exposure and risk assessments in occupational settings.…”
Section: Discussionsupporting
confidence: 74%
“…Literature on workplace UFP chemical composition is currently relatively scarce ( Ntziachristos et al , 2007 ; Terzano et al , 2010 ; Viana et al, 2015 , 2014 ; Corsini et al , 2017 ; Ozgen et al , 2017 ; Mendes et al , 2018 ; Gonzalez-Pech et al , 2019 ), one of the reasons being that it is frequently difficult to obtain enough released material for a proper characterization and more so for toxicological testing ( Kuhlbusch et al , 2018 ). As a result, the characterization of bulk UFP chemical composition for exposure and toxicity assessments still remains a challenge, evidenced by an increasing interest in assessing the concentrations and physico-chemical properties of incidental UFPs in workplaces ( Curwin and Bertke, 2011 ; Stone et al , 2017 ; Viitanen et al , 2017 ; Gonzalez-Pech et al , 2019 ; Keyter et al , 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The nanoparticle fraction of welding fume is typically less than half the total mass [70], so nylon screens are effective in sampling welding fume for one-hour or less. Nylon screens were also used for area samples of metal gouging and lancing side-by-side with inhalable, thoracic and respirable samplers [74]. Nanoparticles averaged around 170 nm in fume during gouging and around 30 nm during lancing.…”
Section: It's All About the Size: How Should We Measure Exposure To Nmentioning
confidence: 99%
“…3,4 Studies have shown particle agglomerates produced by hot working processes typically range in size from 0.05 μm to 20 μm. 5 Amongst them, particles with a size smaller than pollutants, and has important guiding significance for ensuring the health of operators and reducing damage to the environment.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Studies have shown particle agglomerates produced by hot working processes typically range in size from 0.05 μm to 20 μm. 5 Amongst them, particles with a size smaller than 10 μm can enter the human body through the respiratory system, which may cause serious injury to operators. 68 How to scientifically evaluate the diffusion process of the high-temperature particles is helpful for the control of such pollutants, and has important guiding significance for ensuring the health of operators and reducing damage to the environment.…”
Section: Introductionmentioning
confidence: 99%